Divide 61/23 and 36/93

61
23
÷
36
93
=
6
235
276

What is 61/23 ÷ 36/93

61
23
÷
36
93
=

keep the first fraction the same, and flip the second fraction so that the numerator becomes denominator and the denominator becomes numerator, then multiply numerators together and denominator together

61
23
÷
36
93
=
61 x 93
23 x 36
=
5673
828

Simplify the fraction

Divide each part of the fraction with the greatest common factor to simplify the fraction

5673
828
=
5673 ÷ 3
828 ÷ 3
=
1891
276

Because the numerator greater than the denominator, so we have an improper fraction, which means we can simplify it by converting the improper fraction to a mixed number.

Improper fraction to mixed number, get the whole number by dividing the numerator with the denominator, then subtract the numerator by the whole number multiplied by the denominator.

1891
276
=
1891 ÷ 276 = 6 +
1891 - (6 x 276)
276
=
6
235
276

Fraction Calculator

📌 Negative signs in fractions

Positive Fractions

-1
-2
=
-
1
-2
=
-
-1
2
=
1
2

Negative Fractions

-1
2
=
1
-2
=
-
-1
-2
=
-
1
2